Audit quality and decision-making in small companies. Issue 9 (30th September 2014) - Ojala, Hannu; Niskanen, Mervi; Collis, Jill; Pajunen, Kati
Abstract : Purpose: – This paper aims to focus on economic consequences of audit outcomes by investigating the concept of audit quality operationalised as seven components of audit benefits to owner-managers of small companies. Design/methodology/approach: – The authors analyse survey data collected in 2013 from 642 small private companies above the audit exemption threshold in Finland. Findings: – No significant association was found between engagement of a Big 4 auditor (proxy for audit quality) and any of the audit benefits tested. However, the results provide consistent evidence of a positive relationship between the owner-manager's perception of the competence and reliability of the external accountant and the perceived benefits of audit. It was also found that companies which do not incorporate e-processes in the accounting system are more likely to value the internal control benefits provided by audit. Research limitations/implications: – Small business surveys suffer from poor response rates. To some extent, the authors overcame this problem by using two focused sampling frames and reminders. Care must be taken when generalising the results, as the definition of "small" varies across jurisdictions. Originality/value: – By focusing on small private companies, the research contributes to the audit quality literature. Contrary to studies of listed companies, the authors conclude that use of a Big 4 auditor is not a sufficient surrogate for audit quality in small companies. The authors go beyond aggregate measures of audit quality used in previous studies and identify specific audit benefits.